Pengelolaan Aplikasi Web E-Surat Dapat Meningkatkan Kinerja Pada RSUD Waluyo Jati Kraksaan - Hermanto Hermanto; Izzeti Fatinah (Ecobuss, 2022)
Mail management in an organization is important because it will support performance through information fluency, time efficiency, and labor efficiency, This study intends to find out how the management of e-mail Web applications improves performance at Waluyo Jati Kraksaan Hospital. The research used field research with qualitative descriptive methods, data sources from observation, and in-depth interviews with informants, Data credibility test using triangulation technique with relatively the same questions from at least three different sources, with data collection, data reduction, data presentation, and drawing conclusions analysis techniques, The results obtained are that mail management via web e-mail, seen from the aspect of time and labor efficiency, can improve the performance of Waluyo Jati Kraksaan Hospital. Things that need attention for smooth work are the stability of the existing internet system and network. Keywords: Keywords: Management, web e-mail, Application, Performance, and Hospital